Are New Secondary Schools Built Where They are Needed Most in Uganda? Comparing Catholic with Public and Other Private Schools. Issue 2 (2nd April 2020) - Wodon, Quentin
Abstract : Low income countries in sub-Saharan Africa are confronted with a major challenge in terms of expanding access to secondary education. This is also the case in Uganda. This article considers two questions. First, where should new secondary schools be built if the aim is to reduce geographic disparities in access? Second, have new schools, and in particular faith-based schools, been built in the areas that need schools the most? The analysis considers Catholic as well as public and other private schools. Results suggest that new schools are often not located in the areas that need them the most.